Mafb deficiency in myeloid cells increases susceptibility to Mycobacterium tuberculosis infection in mice - Hikichi, Haruka; Nakamura, Hajime; Omori, Shiho; Seto, Shintaro; Hijikata, Minako; Hamada, Michito; Takahashi, Satoru; Keicho, Naoto (Frontiers in Immunology, 2026)
v-Maf avian musculoaponeurotic fibrosarcoma oncogene homolog B (MAFB) is a candidate gene associated with early tuberculosis onset identified by a genome-wide association study. Here, we investigated the role of Mafb in susceptibility to Mycobacterium tuberculosis (Mtb) infection in myeloid-specific Mafb-knockout (Mafb-cKO) mice. Mtb infection was performed both in vitro using bone marrow-derived macrophages (BMMs) from Mafb-cKO mice and in vivo in Mafb-cKO mice. The absence of Mafb promoted Mtb proliferation in BMMs. RNA sequencing (RNA-seq) revealed activation of the metabolic process and impairment of the response to type I interferons (IFNs) in Mtb-infected BMMs from Mafb-cKO mice, which conforms to our previous findings in Mtb-infected human macrophages with MAFB knockdown. Mafb deficiency increased mortality and bacterial burden in the lungs and spleens during Mtb infection in mice. RNA-seq revealed weakened leukocyte or lymphocyte chemotaxis in Mtb-infected Mafb-cKO mouse lungs. Flow cytometry demonstrated an alteration in the proportion of immune cells in Mtb-infected mouse lungs due to Mafb deficiency. Together, Mafb in myeloid cells is involved not only in the functional antibacterial process of macrophages but also in immune cell recruitment in the lungs, thereby contributing to host defense against Mtb infection.